Effect of genotype by environment interactions on quality parameters and grain yield of durum wheat - FAWZIA BOUCHETAT; RAFIKA GHANAI; SARA HIMOUR; SARA BOUAROUDJ; LEILA ALLAL BENFKIH (Society for Indonesian Biodiversity, 2023)
Abstract. Bouchetat F, Ghana R, Himour S, Bouaroudj S, Benfikh LA. 2023. Effect of genotype by environment interactions on quality parameters and grain yield of durum wheat. Biodiversitas 24: 5565-5571. Two experimental trials were conducted at different bioclimatic levels, with the aim to investigate the effect of genotype x environment (Gx E) interaction on grain yield and technological parameters of eight durum wheat (Triticum durum Desf.) varieties. The experiment was set up in a randomized complete block with three replications. The results showed a high Gx E effect on the expression of all evaluated traits. Varieties V4 and V1 with respectively, (24.95 q/ha and 24.73 q/ha) exhibited the highest average yield values across targeted environments. Averaged over the variety main effect, a significant difference of 42 q/ha, in favor of a humid environment, came out for yield. Varieties V3 (84.1 kg/hl) and V6 (83.36 kg/hl) demonstrated the best average specific weight values ??per hectolitre. Similarly, V2; V3; V5 and V7 had the highest rates of black point, while V2 shawled resistance to vitreous kernels (4.33 %). The V3 variety was strongly resistant to grain scalding (2.16 %). The highest levels of protein content were obtained in V6 and V4 (13.38 %; 13.3 %). Varieties: V3; V6 and V1 expressed the best wet gluten content (27.7 %; 26.15 % and 26.13 %). Indeed, the results obtained indicate that each variety is expressed by a particular behavior in relation to environmental diversity.